Kesiapan Sistem Pendidikan Indonesia untuk Pendidikan Inklusif: Analisis Regulasi, Infrastruktur, dan SDM - Delis Ahlia; Abd. Rozak (Indonesian Journal of Islamic Educational Management, 2025)
Inclusive education is a fundamental right of every individual and has become a global and national agenda. In Indonesia, although a legal framework has been established, the implementation of inclusive education still faces significant challenges, particularly in relation to regulations, infrastructure, and human resources. This study aims to analyze the readiness of the education system in Indonesia in implementing inclusive education through a qualitative literature review approach. Data were collected from various scientific literature, government policies, and related reports. Data analysis was conducted through three main stages, namely information extraction from selected sources, data classification into key themes, and critical synthesis to formulate comprehensive conclusions. The results of the study indicate that the main obstacles include the misalignment of central and regional regulations, lack of infrastructure accessibility, limited teacher competence, and social stigma. Synergy between policy, infrastructure investment, human resource capacity building, and school culture change is needed to achieve optimal inclusive education. Research recommendations include regulatory harmonization, adequate budget allocation, ongoing teacher training, and public awareness campaigns